2000
DOI: 10.1002/etc.5620191013
|View full text |Cite
|
Sign up to set email alerts
|

Predicting ready biodegradability in the Japanese ministry of international trade and industry test

Abstract: Abstract-Two new predictive models for assessing a chemical's biodegradability in the Japanese Ministry of International Trade and Industry (MITI) ready biodegradation test have been developed. The new methods use an approach similar to that in the existing BIOWIN᭧ program, in which the probability of rapid biodegradation is estimated by means of multiple linear or nonlinear regression against counts of 36 chemical substructures (molecular fragments) plus molecular weight (mol wt). The data set used to develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
65
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(74 citation statements)
references
References 23 publications
9
65
0
Order By: Relevance
“…Most uses of QACs, and especially the high-volume fabric softeners, lead to their release to municipal wastewater treatment systems. The fabric softener market is dominated by dialkyl quaternaries, in which hydrophobicity is imparted to the molecule by two linear alkyl chains in the C [10][11][12][13][14][15][16][17][18] range. The hydrophobe is generally derived from purified animal fat (tallow) and consists of a mixture chiefly in the C 16 -C 18 (tallow fatty acids) range.…”
Section: Dialkyl Quaternariesmentioning
confidence: 99%
“…Most uses of QACs, and especially the high-volume fabric softeners, lead to their release to municipal wastewater treatment systems. The fabric softener market is dominated by dialkyl quaternaries, in which hydrophobicity is imparted to the molecule by two linear alkyl chains in the C [10][11][12][13][14][15][16][17][18] range. The hydrophobe is generally derived from purified animal fat (tallow) and consists of a mixture chiefly in the C 16 -C 18 (tallow fatty acids) range.…”
Section: Dialkyl Quaternariesmentioning
confidence: 99%
“…Details on the model and structural alerts can be found in Tunkel et al (2000) Please note that only the structural alerts have been implemented as a profiler. No predictions on biodegradability are provided as a result of using the profiler.…”
Section: Biowin Miti Fragmentsmentioning
confidence: 99%
“…Gamberger et al [8], for example, created two different rules, each designed to best predict data from one or the other dataset. The commonly used BIOWIN model package recommended by the EU Risk Ranking Method [14] includes separate linear and non-linear models built from the MITI-I and the BIODEG data [11,18]. It has been reported that due to cross correlations, it is possible to develop a model that fits the training set data well but is not reliable as a predictor for chemicals outside the training set [19].…”
Section: Data Availability For Environmental Fate Assessment Of Chemimentioning
confidence: 99%